The Dharmashashtra: Understanding ModernDay Conflictual Behaviour Through The Lenses Of Ancient Hindu Texts - Dutta, Rhitwique; Dutta, Kaushik (International Journal of Psychosocial Rehabilitation, 2023)
This study aims to explore the nature of conflict and violence in our reality through the lenses of Dharmashashtra. Our study is not aimed at providing a solution to conflicts, instead, we have conceptualized factors that are responsible for disturbing the delicate cosmic balance. This piece explores the impact of compartmentalization of ancient Indian philosophies within a specific time and content. However, this could have catastrophic consequences as the interpretation of various thoughts or ideas in the Vedas have continuity across time. The Varna system is overly emphasized as an Indian curse that has no solution; however, this became a negative aspect only when the British defined it clearly in an objective manner. This also led to an eternally conflict-oriented societal formation in India. Our goal is to break away from the objective and clear interpretation of Dharmashashtra, keeping the discussions ongoing throughout our entire existence is key to realizing a society that is at a balance.